Finite element analysis of bending of open section composite beams - Tan, Wee Peng (Nanyang Technological University, 2024)
The objective of this Final Year Project is to investigate the bending behaviour of composite I-beams made with Carbon Fibre Reinforced Polymer (CFRP) and Toray T700, focusing on different ply configurations (4-ply and 8-ply) and web heights (40 mm and 60 mm). The study utilizes Finite Element Analysis (FEA) in ANSYS to simulate the structural response of these I-beams under three-point bending tests. Results indicated that increasing the ply count and web height enhances the load-bearing capacity and reduces deformation, with carbon fibre outperforming Toray T700 due to its superior mechanical properties. The 8-ply, 60 mm web height I-beam configuration exhibited the highest stiffness and minimal deflection, demonstrating its suitability for high-performance applications. The results of this study contributed valuable insights into optimizing composite beam design, contributing to the development of lightweight, efficient, and structurally robust components for aerospace, automotive, and civil engineering industries.